The Effect of Preformed Metal Crowns on Primary Molars’ Exfoliation Time - Omar A. El Meligy; Nermeen A. Alhosini; Sara M. Bagher (Journal of King Abdulaziz University: Medical Sciences, 2023)
Many factors contribute to the exfoliation of teeth. However, none of the local factors mentioned in the literature was the quality of coronal restorations. The aim of this research was to study the relation between restoring primary molars with preformed metal crowns and exfoliation process. Five hundred and fifty dental records of healthy children undergoing comprehensive dental treatment at the Faculty of Dentistry, King Abdulaziz University hospital in Jeddah were reviewed. Out of the 550 reviewed dental records, 140 records satisfied the inclusion criteria. Exfoliation time was recorded as on time, early or late. Undesirable exfoliation time was shown in 39 (27.9%) of the crowned primary molars (experimental) group compared to zero (0.00%) of primary molars in the control group. There was a statistically significant difference between both groups regarding the exfoliation time. However, within the experimental group, a relationship between crowned primary molars with pulp therapy or crowned primary molars without pulp therapy and exfoliation time was reported. This study showed no statistically significant difference between both groups, respectively. Our data suggest that preformed metal crowns might affect the exfoliation time of primary molars by either accelerating or delaying exfoliation.